2022
DOI: 10.1108/ijchm-09-2021-1132
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-tourism well-being: the interplays of salient and enduring determinants

Abstract: Purpose The purpose of this study is to develop and test an integrated structural gastro-tourism wellbeing model consisting of food-related lifestyle and leisure attitude as a precursor of the consumption enjoyment of the gastro-tourism experience with satisfaction, life domain outcomes, tourism autobiographical memory and life satisfaction as outcomes of the consumption enjoyment. Design/methodology/approach The conceptual model was assessed with quantitative data collected from tourists based on their deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 80 publications
0
21
0
3
Order By: Relevance
“…In addition, given that some studies have shown how tourists change their dietary habits while on holiday (e.g. Santos et al, 2020), another line of research could be to explore whether consumer behaviors tied to F&B within wellness experiences (both hedonic and eudaimonic) are: (a) consistent with tourists' lifestyles (Kesgin et al, 2022) and (b) transformational to the point of influencing post-vacation attitudes toward food (Neuhofer et al, 2021).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, given that some studies have shown how tourists change their dietary habits while on holiday (e.g. Santos et al, 2020), another line of research could be to explore whether consumer behaviors tied to F&B within wellness experiences (both hedonic and eudaimonic) are: (a) consistent with tourists' lifestyles (Kesgin et al, 2022) and (b) transformational to the point of influencing post-vacation attitudes toward food (Neuhofer et al, 2021).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…By focusing the present study within the context of wellness tourism, we can contribute to filling the gap in the extant gastronomic tourism literature. At the same time, we explore the emerging topic of the relationship between food and wellness (Kesgin et al, 2022;Tiwari and Hashmi, 2022;Batat et al, 2019).…”
Section: Introduction and Purpose Of The Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The article of Kesgin et al (2022) represents the first attempt to link gastronomy tourism to life satisfaction. It describes the determinant of gastro-tourism well-being through a newly developed model, which considers food-related lifestyle and leisure attitude as antecedents of consumption experience and satisfaction in gastronomy experiences.…”
Section: Contributionsmentioning
confidence: 99%